Analysis of Factors Influencing Working Poverty in Java - Imama, Febryanti Nur; Kresna Sakti, Rachmad (Journal of Development Economic and Social Studies, 2026)
The phenomenon of working poverty demonstrates that having a job does not always guarantee an escape from poverty. This situation also occurs in Java, the center of national economic activity with a high labor participation rate. Despite relatively high labor absorption, the welfare of some workers remains low, indicating structural problems in the labor market. However, empirical studies on the factors influencing working poverty in Indonesia, particularly in Java, are still limited. This study aims to analyze the factors that influence the likelihood of someone becoming working poor in Java, considering individual, occupational, and household factors. This study uses a quantitative approach using microdata from the February 2025 National Labor Force Survey (Sakernas) analyzed using binary logistic regression. The results show that individual and occupational factors significantly influence working poverty status, while household factors have no significant effect. These findings indicate that working poverty in Java is related to job quality and stability and emphasize the importance of improving job quality and more inclusive labor protection.